Severity and disease control before house dust mite immunotherapy initiation: ANTARES a French observational survey. Issue 1 (December 2016) - Demoly, Pascal; Broué-Chabbert, Anne; Wessel, François; Chartier, Antoine
Abstract Background Allergen immunotherapy (AIT) may be prescribed for patients with allergic rhinitis (AR) induced by house dust mites (HDM) whether asthma is present or not. Current guidelines provide insufficient support for therapeutic management strategy of these patients. Allergists however have long-term experience with AIT. This study aims to describe the characteristics of the patients seen in clinical practice with HDM allergy and the process used to determine whether AIT should be initiated. Methods This was an observational, multicenter, prospective and cross-sectional study, conducted in France from 2013 to 2014 with a representative sample of allergy specialists. Any patient over 5 years of age with confirmed HDM allergy untreated with AIT within the last 12 months was eligible. Data were prospectively collected using physician and patient questionnaires. Results A total of 1589 patients (60 % adults, 40 % children) were included by 195 randomly selected allergists. A subgroup of 1212 patients (median age: 22 years; 52 % women) were selected for AIT treatment with a median time of AR diagnosis of 3 years. Amongst these, 59 % had a moderate to severe persistent AR according to AR and its Impact on Asthma guidelines, 57.5 % were polysensitized, and 56.5 % also suffered from conjunctivitis (median rhinitis total symptom score: 11). Asthma was present in 42 % of patients, and was controlled according to Global Initiative for Asthma guidelines in 62 % of patients. The asthma control questionnaire score was 1–1.5 in 20 % and ≥1.5 in 37 % of patients. A total of 57 % patients received a prescription of ≥2 medications (mainly antihistamines). Usual daily activities and sleep quality were slightly-to-moderately impaired as the mean rhinoconjunctivitis quality of life questionnaire score was 2.7 ± 1.5. The major driver of AIT prescription is AR uncontrolled by previous medications leading to patient dissatisfaction. Conclusions HDM-AR associated conjunctivitis was present in 60 % and asthma in 40 % of cases. In >40 % of these cases, asthma was inadequately controlled at the start of AIT.